A Mobile Sign Language Dictionary: Enhancing Communication for the Deaf and Mute - Rakhmadi, Aris; Wulandari, Novita Desi; Rosad, Safiq; Syukri, Muhammad (Fakultas Teknik Universitas 17 Agustus 1945 Cirebon, 2025)
Communication is fundamental to human interaction, yet individuals who are deaf or speech-impaired often face barriers due to limited accessibility to sign language resources. This study presents the development of a mobile sign language dictionary designed to enhance communication and learning. Traditional sign language dictionaries, whether in printed or video formats, present challenges in accessibility, usability, and portability. In contrast, a mobile application offers an interactive, efficient, and user-friendly solution. The proposed application integrates gesture recognition, video demonstrations, and text-based explanations to facilitate sign language learning. By leveraging artificial intelligence (AI) and cloud-based storage, the app ensures accurate sign recognition and provides a comprehensive database of gestures, including letters, numbers, root words, prefixes, suffixes, and commonly used phrases. A structured methodology involving requirement analysis, data collection, design, development, testing, and revision was applied to develop a functional and accessible tool. User testing demonstrated high engagement and learning effectiveness, with 85% of participants reporting increased comfort with mobile learning tools, 82.5% finding the app beneficial for sign language acquisition, and 90% improving their familiarity with sign words. These results confirm that a mobile sign language dictionary is an efficient educational tool that fosters inclusivity and communication accessibility. Future enhancements, including database expansion, additional sign language dialects, and interactive exercises, can further improve the application’s impact.